Pemerolehan Bahasa Pertama pada Anak Abnormal: Disleksia - Andini Fitria; Nurwahyuni Nurwahyuni; Regita Firjianti; Fatmawati Fatmawati (UIR Press, 2023)
Dyslexia can involve difficulties with spoken language. Research has shown that drawing children's attention to the aspects of spoken language that are most important in the reading process can help with early literacy development. Evidence also suggests that dyslexia is associated with differences in how the brain processes spoken and written language. The characterization of dyslexia as a language-based disorder may be confusing in light of another prominent language disorder, language developmental disorder. children with developmental language disorders have unexpected deficits in language skills despite adequate environmental stimulation and cognitive abilities without neurological impairment. Dyslexia impacts language memory and word acquisition. Most people have incidents where they can't remember the words they want to use. For those who don't have language limitations, it happens occasionally - perhaps due to fatigue or the infrequent use of certain words. However, children with dyslexia may experience it more frequently, affecting their speech.